2016
DOI: 10.1371/journal.pone.0165405
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Diseases Caused by Mutations in Genes Not Specifically Associated with the Clinical Diagnosis

Abstract: PurposeWhen seeking a confirmed molecular diagnosis in the research setting, patients with one descriptive diagnosis of retinal disease could carry pathogenic variants in genes not specifically associated with that description. However, this event has not been evaluated systematically in clinical diagnostic laboratories that validate fully all target genes to minimize false negatives/positives.MethodsWe performed targeted next-generation sequencing analysis on 207 ocular disease-related genes for 42 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…One likely reason is that disease‐causing variants within non‐coding regions may remain undetected using standard targeted NGS. Other possible explanations include mutations in genes that have not yet been associated with retinal dystrophies, hypomorphic variants or genetic testing of patients with disease entities mimicking RP (eg, autoimmune retinopathy in patients with cancer or autoimmune disease), which all may potentially be associated with a specific retinal phenotype and/or systemic diseases . Hence, we hypothesized that genetically unsolved RP‐patients may reveal characteristics that differ from genetically solved RP‐patients.…”
Section: Introductionmentioning
confidence: 99%
“…One likely reason is that disease‐causing variants within non‐coding regions may remain undetected using standard targeted NGS. Other possible explanations include mutations in genes that have not yet been associated with retinal dystrophies, hypomorphic variants or genetic testing of patients with disease entities mimicking RP (eg, autoimmune retinopathy in patients with cancer or autoimmune disease), which all may potentially be associated with a specific retinal phenotype and/or systemic diseases . Hence, we hypothesized that genetically unsolved RP‐patients may reveal characteristics that differ from genetically solved RP‐patients.…”
Section: Introductionmentioning
confidence: 99%
“…It remains possible that variants of RIMS1 are associated with a dominant disease given the probability of loss-of-function intolerance (pLI) of the gene is 0.99 (0–1 scale) in the gnomAD dataset suggesting that haploinsufficiency is not tolerated, and that murine knockout exhibits a complex neurological phenotype. 16 However, no proven cases of inherited disease consequent upon loss of function variants exist to date, 12 14 to our knowledge, and no cases of confirmed RIMS1 disease are known. In the original publication, affected members of the study also showed enhanced cognition and this may be consequent on the p.Arg820His variant in RIMS1 17 and that co-inheritance of these two phenotypes is coincidental in the family.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, no other compelling evidence for pathogenic variants in RIMS1 have been identified to date. 12 14 The only other report in the literature of the p.Arg820His variant was seen in a simplex patient with RP and a discordant phenotype. 7 …”
Section: Discussionmentioning
confidence: 99%
“…21 22 A later report described a patient with the same RIMS1 variant, but a different phenotype (retinitis pigmentosa), 23 and there have further variants reported, but without detailed evidence to secure a causative relationship. [24][25][26] Implication of AHR in retinal disease comes from a report of a single family. 27 For KIAA1549, there is a single report of two families.…”
Section: Discussionmentioning
confidence: 99%